New materials based on modified synthetic Nb2O5 as photocatalyst for oxidation of organic contaminants - Esteves, Andre; Oliveira, Luiz C. A.; Ramalho, Teodorico C.; Goncalves, Maraisa; Anastacio, Alexandre S.; Carvalho, Hudson W. P. [UNESP] (Elsevier B.V., 2008)
Novel materials based on niobia (Nb2O5) destined to oxidize an organic compound in aqueous medium via heterogeneous photocatalysis after chemical modification were synthesized. Niobia was modified by the doping with molybdenum or tungsten and also treated with H2O2. The analysis of the products from methylene blue dye oxidation, with electrospray ionization mass spectrometry, showed that the dye was Successively oxidized to different intermediate compounds. These results strongly Suggest that the oxidation of the organic dye involves oxidizing species mainly generated after the modification of the niobia with Mo or W and also the previous treatment with H2O2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Synthetic niobia; Doped; Photocatalysis